Research trends on lymphedema after mastectomy for breast cancer patients from 2000 to 2023: a scientometric analysis - Chen, Ling; Zheng, Yuxian; Zheng, Daitian; Li, Zhiyang; Chen, Hongwu; Chen, Chujun; Yu, Shuxian (Frontiers in Oncology, 2025)
BackgroundBreast cancer-related lymphedema (BCRL) is a common and debilitating complication following breast cancer treatment. Despite its significant impact on patients’ quality of life, bibliometric analyses focusing on BCRL are scarce. This study aims to explore global research trends on BCRL from 2000 to 2023, identify existing knowledge gaps, and highlight emerging focus areas through a bibliometric approach.MethodsA comprehensive search was conducted using the Web of Science (WOS) database to retrieve literature published between January 2000 and November 2023. Bibliometric analyses and visualizations were performed using R Studio, CiteSpace, and VOSviewer. Key data extracted included publication trends, contributing countries and institutions, leading authors, journals, research categories, and keywords. Outcome measures for analysis included the number of publications, citation counts, author productivity, and keyword co-occurrence.ResultsA total of 919 eligible publications from 52 countries and regions, 1,163 institutions, and 3,550 authors were identified. These publications appeared in 255 journals, with “Lymphology” emerging as the journal with the highest citation count. The USA was the most prolific contributor to the field. The annual number of publications demonstrated a consistent upward trend. Keyword co-occurrence analysis revealed prominent research hotspots, including “lymphedema,” “women,” “breast cancer,” “arm lymphedema,” and “quality of life.” Emerging keyword trends from 2021 to 2023 highlighted “prevention” and “validity” as pivotal research frontiers.ConclusionsThis bibliometric study highlights the growing interest in breast cancer-related lymphedema research and identifies key areas for future investigation, including prevention, diagnosis, and treatment strategies. The results underscore the need for further exploration of these emerging research areas to improve patient outcomes.